Polyglutamine diseases. (February 2022) - Bunting, Emma L.; Hamilton, Joseph; Tabrizi, Sarah J.
Abstract: Polyglutamine diseases are a collection of nine CAG trinucleotide expansion disorders, presenting with a spectrum of neurological and clinical phenotypes. Recent human, mouse and cell studies of Huntington's disease have highlighted the role of DNA repair genes in somatic expansion of the CAG repeat region, modifying disease pathogenesis. Incomplete splicing of the HTT gene has also been shown to occur in humans, with the resulting exon 1 fragment most probably contributing to the Huntington's disease phenotype. In the spinocerebellar ataxias, studies have converged on transcriptional dysregulation of ion channels as a key disease modifier. In addition, advances have been made in understanding how increased levels of toxic, polyglutamine-expanded proteins can arise in the spinocerebellar ataxias through post-transcriptional and -translational modifications and autophagic mechanisms. Recent studies in spinal and bulbar muscular atrophy implicate similar pathogenic pathways to the more common polyglutamine diseases, highlighting autophagy stimulation as a potential therapeutic target. Finally, the therapeutic use of antisense oligonucleotides in several polyglutamine diseases has shown preclinical benefits and serves as potential future therapies in humans. Highlights: DNA repair genes drive somatic expansion in Huntington's disease. Incomplete splicing of human HTT generates the toxic exon 1 fragment. Ion channel dysregulation is a shared mechanism across multiple polyglutamine spinocerebellar ataxias. ATXN1 's unusually long 5′ untranslated region plays a key role in the regulation of its expression. Antisense oligonucleotides may be potential therapeutics for several polyglutamine disorders.